Antifascist memory revisited: Hungarian historical exhibitions in Oświęcim and Paris, 1965. (October 2022) - Kékesi, Zoltán; Zombory, Máté
The article challenges the widely shared thesis in memory studies that the antifascist memory of the Second World War suppressed the Holocaust. Instead of exploring exceptions to this rule by looking for single cases of antifascist memory that represent some aspects of the Holocaust, we argue that antifascist memory presented a distinct cultural regime for remembering the past. Our claim is that antifascist memory, understood as a particular historical phenomenon on a transnational scale, opened up specific ways to commemorate the Jewish genocide. Our article relies on two pillars: first, on recent memory studies scholarship that challenged "the myth of silence" in relation to the postwar decades; second, on recent studies revisiting antifascism itself, demonstrating its transnational and ideologically diverse nature. We argue that a contested but at least until the 1970s still commonly held pan-European antifascist legacy fostered not only intra-Eastern bloc but also cross–Cold War mnemonic cooperation. We present an empirical comparative study that discusses the 1965 Hungarian exhibition at the State Museum Auschwitz-Birkenau and the Hungarian section at the permanent exhibition at the Museum of the Memorial of the Unknown Jewish Martyr in Paris that opened in the same year. Based on archival documents in Budapest, Auschwitz-Birkenau, and Paris, we prove that both exhibitions displayed a coherent, historically accurate, and comprehensive account of the genocide that articulated unambiguously the Jewish identity of those perished and persecuted. At the same time, they both operated under discursive conditions informed by antifascist legacies in Poland, Hungary, and France.